Analisis Kinerja Keuangan pada Koperasi Mitra Karya di Desa Sidakarya Kecamatan Denpasar Selatan - LESTARI, TRI NOVITA; RANTAU, I KETUT; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
An analysis of financial performance at Mitra Karya Cooperative in Sidakarya Village South Denpasar A multi-purpose cooperative is an example of institutions designed for economic empowerment that have succeeded in improving the welfare of society in general and its members in particular. Cooperatives usually assess financial performance by looking at the increase of cash, assets, and profits using profitability ratio analysis. However, performace should also be reviewed using other types of ratio analysis such as liquidity ratios, solvency ratios, and activity ratios as well as trend analysis. This study aims to determine the financial performance of Mitra Karya Multipurpose Cooperative between 2015 to 2019 using financial ratio analysis based on the Regulation of the State Minister for Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 06/Per/M.KUKM/V/2006 and the least squares method to analyze the trend. The results of the analysis show that several types of ratios are classified as not good, namely the current ratio, quick ratio, cash ratio, debt to asset ratio, debt to equity ratio, and total asset turnover. Meanwhile, those belonging to good and bad criteria are the ratio of return on equity and the ratio of return on investment. The results of trend analysis that show an increasing trend are the current ratio, quick ratio, return on investment ratio, return on equity ratio, and total asset turnover. Meanwhile, cash ratio, debt to asset ratio, and debt to equity ratio tended to decline.